Relation between resilience and cigarette/alcohol use in adolescents with mild intellectual disability - Pavlović, Miroslav; Žunić-Pavlović, Vesna; Glumbić, Nenad (Vojnosanitetski pregled, 2021)
Abstract Background/Aim. Resilience is related to the substance use in adolescence. However, little is known about the nature of this relation in adolescents with intellectual disability (ID). The aim of this research was to determine the relation among three domains of resilience (sense of mastery, sense of relatedness and emotional reactivity) and the substance use (cigarettes, alcohol, and marijuana) in adolescents with ID. Methods. The sample consisted of 100 adolescents of both genders with mild ID and aged 13-20 years. The Resiliency Scales for Children and Adolescents were used to assess resilience. Results. In the adolescents with ID, resilience was significantly related to the use of cigarettes (χ2 = 13.384; df = 3; p = 0.004), but not to the use of alcohol (χ2 = 6.789; df =3; p > 0.05). Out of the three assessed domains of resilience, increased emotional reactivity was the only significant predictor of cigarette use. Conclusion. The obtained results suggest that emotional difficulties may increase the risk of cigarette use in adolescents with ID.
Keywords: adolescent; alcohol drinking; intellectual disability; resilience, psychological; smoking